(untitled) (Research, Society and Development, 2021)
Breast cancer can impact different health spheres of patients, since the experience with the treatment is often surrounded by fears and anxieties. It is possible to observe that adverse effects of chemotherapy are common and women with breast cancer may have a high incidence of oral mucositis (OM). Thus, the objective of this review was to discuss the relationship between chemotherapy treatment of breast cancer and the occurrence of oral mucositis. OM is characterized by the appearance of erythema or ulcers in the oral cavity, and its classification varies according to the scale used. The pathophysiology is associated with risk factors, since the treatment administered and the patient’s lifestyle can directly impact the occurrence and progression of OM. Although most cases are mild or moderate, the impact of OM can not be underestimated, even in cases of low symptoms or functional impact, considering oral pain and difficulty in food intake. Thus, it is important that professionals pay attention to the classification, risk factors and possible impacts on health, including the planning of preventive and curative actions in the management of this adverse effect of chemotherapy. Health professionals, including dentists, nurses and doctors must be prepared to deal with cases of OM, promoting integrated actions to reduce the impact of this condition on the health of women with breast cancer.